Individual Risk Factors Influencing Safety Climate in Construction Projects - Erismawati, Ni Kadek Lilis; Lestari, Fatma (FORIKES, 2026)
The construction industry is widely recognized as a sector with a high risk of occupational accidents, despite the implementation of occupational safety and health management systems. Differences in workers’ individual characteristics are believed to influence safety perceptions and behaviors. This study aims to analyze the influence of individual factors on safety climate in construction projects through a systematic literature review. Articles were searched in Google Scholar, PubMed, and Scopus databases using the keywords “individual factors,” “safety climate,” and “construction projects,” with predefined inclusion and exclusion criteria. A total of 7,246 articles were identified, and after systematic screening, 16 studies published between 2021 and 2025 met the eligibility and quality criteria for analysis. The findings indicate that individual factors—including age, gender, education level, work experience, job position, and knowledge—are associated with safety climate perceptions, although the magnitude of their influence varies across studies. Job position emerged as the most consistent factor influencing safety climate, while organizational aspects such as management commitment and supervision remained dominant determinants. This review concludes that individual characteristics contribute to workers’ perceptions of safety climate; however, strengthening organizational-level factors remains essential to support sustainable occupational safety in the construction sector.Keywords: individual factors; safety climate; construction projects